2022
DOI: 10.1111/gcb.16169
|View full text |Cite
|
Sign up to set email alerts
|

Glacier shrinkage will accelerate downstream decomposition of organic matter and alters microbiome structure and function

Abstract: The shrinking of glaciers is among the most iconic consequences of climate change. Despite this, the downstream consequences for ecosystem processes and related microbiome structure and function remain poorly understood. Here, using a space‐for‐time substitution approach across 101 glacier‐fed streams (GFSs) from six major regions worldwide, we investigated how glacier shrinkage is likely to impact the organic matter (OM) decomposition rates of benthic biofilms. To do this, we measured the activities of five c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 121 publications
5
22
0
1
Order By: Relevance
“…Simultaneously, parasitic fungi also foster the release of organic compounds from algae via the 'fungal shunt' 31 . The prevalence of parasitic fungi has been noted previously in GFS 47 and other cryospheric ecosystems 48 ; our analyses further point to the importance of interactions among parasitic fungi and their algal host in proglacial stream biofilms. Along these lines, Mo et al 49 recently suggested that interactions of microeukaryotes between them in the Lena River continental shelf were more stable compared to that of the estuary, potentially explained by variability in salinity.…”
Section: Discussionsupporting
confidence: 82%
“…Simultaneously, parasitic fungi also foster the release of organic compounds from algae via the 'fungal shunt' 31 . The prevalence of parasitic fungi has been noted previously in GFS 47 and other cryospheric ecosystems 48 ; our analyses further point to the importance of interactions among parasitic fungi and their algal host in proglacial stream biofilms. Along these lines, Mo et al 49 recently suggested that interactions of microeukaryotes between them in the Lena River continental shelf were more stable compared to that of the estuary, potentially explained by variability in salinity.…”
Section: Discussionsupporting
confidence: 82%
“…Understanding the nature of these constraints and their impacts on microbial communities in these ecosystems is particularly relevant in light of climate change and the expected predominance of TRIBs in the future. In line with this, our previous work indicated an important role of eukaryotic phototrophs in explaining the differences between GFS and TRIB communities ( 18 , 25 , 26 ). We expect that organic carbon provided by benthic primary producers can alleviate (to some extent) resource limitation in TRIBs and, thus, reduce the importance of selection therein.…”
Section: Introductionsupporting
confidence: 82%
“…In all three proglacial floodplains, we found significant longitudinal changes in community similarity from the GFSs close to the glacier snout to the outlet of the floodplain (Supplementary Figure 11). These patterns are unexpected given the relatively short distances (hundreds of meters) along the longitudinal chronosequence and the high dispersal of microbial cells in GFSs (Ezzat et al, 2022). We attribute this spatial turnover to downstream changes in the GFS environment that may be partially induced by processes (e.g., sedimentary dynamics) in the GFS channel itself, but also by the cumulative influence of the tributaries discharging into the GFS.…”
Section: Community Structure Differs Between Stream Typesmentioning
confidence: 82%
“…This network pattern points to a potential role of Chytridiomycota in structuring biofilm communities in proglacial streams. In fact, Chytridiomycota have received increasing scientific interest as common microparasites of marine and freshwater algae ( Grossart et al, 2019 ; Klawonn et al, 2021 ) as well as in the cryosphere ( Brown et al, 2015 ; Lutz et al, 2015 ; Anesio et al, 2017 ; Rojas-Jimenez et al, 2017 ; Kohler et al, 2022 ) where they may shunt algal carbon to fungal biomass, thereby bypassing the typical microbial loop. Given that vascular plant debris is typically absent in proglacial streams, fungi parasitizing on benthic algae seems intuitive.…”
Section: Resultsmentioning
confidence: 99%